TI_GERICHTE 15.2005.97 vom 27. September 2005 , ricorso. Esigenza di motivazione. Contestazione dello stato di riparto - TI Tribunale d'appello (2005)
ricorso. Esigenza di motivazione. Contestazione dello stato di riparto